Karakterisasi Distribusi Ozon Pada Air Distilasi dan Air Kelapa yang Diproduksi Menggunakan Mesin Lucutan Plasma Berpenghalang Dielektrik Ganda - David Yudianto; Ratih Dewanti Hariyadi; Sukarno Sukarno; Muhammad Nur; Eko Hari Purnomo (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2023)
Ozone produced using plasma technology can act as an antimicrobial agent that could be applied in a sterilization process. A Double Dielectric Barrier Discharge (DDBD) machine has ability to produce ozone in sufficient amount for microbial inactivation. The objective of this study is to characterize the ozone distribution expressed as dissolved ozone in distilled water and coconut water produced using a DDBD machine. The information can be useful for industries to design a commercial sterilization process. The results shows that an oxygen flow rate of 0.2 L/min produces the highest ozone concentration, i.e. 3440 mg/L. In addition, the capacity of the machine is relatively similar to all off oxygen flow rate, i.e., 41.28-43.2 g/hour. The oxygen flow rate of 0.2 L/min produces the highest dissolved ozone concentration, i.e. 0.42 mg/L distilled water. This oxygen flow rate is followed by its best kinetic model based on its linear portion during dissolved ozone penetration. A zero order model could describe this penetration process well, including its best k value of 0.0292 mg/L per minute with the highest dissolved ozone concentration among other oxygen flow rates. Besides, distilled water could represent dissolved ozone penetration in coconut water. Ozone gas and dissolved ozone concentration have possitive corellation with R-square value of 0.8934.